Concept of automation design and preparing production of orientation system actuator of space devices based on T-FLEX programme product - Dmitriev V. S. Viktor Stepanovich (2001, 2001)
Competition in fields connected with developing devices for space purposes, automation of design and preparing production is becoming the most important condition of survival and maintenance of a product on the competitive level. The last gives essential reduction of terms of design and vastly raises quality of design devices. The most efficient system, covering automation of all stages of design and preparing production from preliminary design to preparing the programs for machine tools with NPC and designing a rig. We think it is rational to make computer automation design systems and prepare production using T-FLEX programs (Top Systems, Moscow): T-FLEX 2D, design of draughts and parameterization; T-FLEX 3D, making the three-dimensional models and three-dimensional adjustment models; T-FLEX DOCs, conduct of projects and document rate; T-FLEX/Techno About, designing a technology; T-FLEX/NPC, preparing the programs for machine tools with (NPC); T-FLEX/Stamps and T-FLEX/Dies, designing a rig, All T-FLEX programs completely correspond to requirements on automation of design and preparing production of orientation systems actuator.